(untitled) (Bangladesh Journal of Nuclear Medicine, 2017)
Introduction: Osteoporosis or low bone mass is one of the systemic effects of the chronic obstructive pulmonary disease (COPD). Fracture may occur as a complication of low bone mass in these patients that increases the morbidity. There is lack of awareness about the decreased bone mass in these patients. There is significant need to screen those patients who are at risk, so that early diagnosis can be made and preventive and or therapeutic measures can be taken to avoid the consequences of osteoporosis. Dual energy X-ray absorptiometry (DEXA) is the current gold standard for the diagnosis of osteoporosis or low bone mass. Objective: To evaluate the bone mineral density of the chronic obstructive pulmonary disease patients with dual energy X-ray absorptiometry and compare with the controls (non-COPD patients). Method: In the period of January 2010 to December 2010 a total number of 100 subjects were included in the study. Among them fifty patients were with chronic obstructive pulmonary disease and fifty apparently healthy persons without chronic lung diseases taken as comparison group controls. Bone mineral density (BMD) of lower lumber spine (L1-L4) and left femoral neck were measured by Lunar DPX pro (GE) scanner. Low BMD was defined according to World Health Organization (WHO) criteria based on T score of patients and were compared with the controls. Results: BMD was significantly low in COPD patients than in control group. At femoral neck, low BMD was found among 84% of patients with COPD and 36% of controls without COPD. At lumber spine low BMD was found among 86% of patients with COPD and 60% of patients without COPD. Conclusion: This study suggests that bone mineral density is low in chronic obstructive pulmonary disease. Bangladesh J. Nuclear Med. 18(1): 27-31, January 2015